Menelisik Kebijakan Moderasi Beragama Dalam Pandangan Kebebasan Beragama Atau Berkeyakinan - Elkristi Ferdinan Manuel (Universitas Cokroaminoto Yogyakarta, 2026)
This study critically examines religious moderation in Indonesia by examining how the policy operates within the context of freedom of religion or belief (KBB), particularly for minority groups. Top-down moderation creates